2008
DOI: 10.1093/glycob/cwn085
|View full text |Cite
|
Sign up to set email alerts
|

Structure, biology, evolution, and medical importance of sulfated fucans and galactans

Abstract: Sulfated fucans and galactans are strongly anionic polysaccharides found in marine organisms. Their structures vary among species, but their major features are conserved among phyla. Sulfated fucans are found in marine brown algae and echinoderms, whereas sulfated galactans occur in red and green algae, marine angiosperms, tunicates (ascidians), and sea urchins. Polysaccharides with 3-linked, beta-galactose units are highly conserved in some taxonomic groups of marine organisms and show a strong tendency towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
252
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(267 citation statements)
references
References 93 publications
10
252
1
4
Order By: Relevance
“…Increasing research on algal polysaccharides, in native form or their derivatives, have revealed a variety of biological activities including anti-virus (Ghosh, Chattopadhyay et al 2009;Harden, Falshaw et al 2009), antioxidant (Josephine, Amudha et al 2007; Rocha de Souza, Marques et al 2007), anti-tumor (Zhou, Sun et al 2004;YamasakiMiyamoto, Yamasaki et al 2009), anticoagulant/anti-thrombotic (Pereira, Mulloy et al 1999;Pomin and Mourco 2008), and immuno-inflammatory activities (Groth, Grunewald et al 2009;Yang, Yu et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Increasing research on algal polysaccharides, in native form or their derivatives, have revealed a variety of biological activities including anti-virus (Ghosh, Chattopadhyay et al 2009;Harden, Falshaw et al 2009), antioxidant (Josephine, Amudha et al 2007; Rocha de Souza, Marques et al 2007), anti-tumor (Zhou, Sun et al 2004;YamasakiMiyamoto, Yamasaki et al 2009), anticoagulant/anti-thrombotic (Pereira, Mulloy et al 1999;Pomin and Mourco 2008), and immuno-inflammatory activities (Groth, Grunewald et al 2009;Yang, Yu et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Sulfated polysaccharides (SPs) make up a group of biopolymers that occur in a great variety of marine organisms (Stephen, 1995;Hayashi et al, 1996;Mourão and Pereira, 1999;Aquino et al, 2005;Pomin and Mourão, 2008;Robic et al, 2009;Rodrigues et al, 2009a;Mestechkina and Shcherbukhin, 2010;Rodrigues et al, 2010). In red seaweed, SPs are known as sulfated galactans, and are found in carrageenans and agarans (Melo et al, 2002;Marinho-Soriano, 2006;Pomin and Mourão, 2008;Campo et al, 2009;Silva et al, 2010;Rodrigues et al, 2011a). These highly charged macromolecules (presence of sulfate groups) exhibit chemical structures of complex and heterogeneous nature, playing an important role in ionic, mechanical and osmotic functions, and are constituents of the extracellular matrix of marine algae (Kloareg and Quatrano, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the galactan isolated from the red marine alga G. crinale presented inflammatory activity in the experimental model of rat paw edema. Inflammatory effects of SP of red algae have already been demonstrated (Di Rosa et al, 1971;Damas, 1980;Pomin & Mourão, 2008;Assreuy et al, 2008Assreuy et al, , 2010Lins et al, 2009). The inflammatory effect of λ carrageenan, already demonstrated in literature, show different profile of response compared to SG-Gc.…”
Section: Discussionmentioning
confidence: 94%
“…Edematogenic activity of a sulfated galactan from the red marine algae Gelidium crinale their inflammatory effects (Di Rosa et al, 1971;Damas, 1980;Pomin & Mourão, 2008). Among the main commercialized carrageenans (κ, ι, and λ), κ and ι form gelling polymers, whereas λ is a nongelling due to its content of three sulfate groups (2-sulfate in 3-β-d-Galp and 2,6-dissulfate in α-d-Galp) without the presence of 3,6-anhydro in α-galactopyranose (McCandless, 1981;Perez et al, 1992) ( Figure 1B).…”
Section: Short Communicationmentioning
confidence: 99%